DEVELOPMENT OF THE ANDROID-BASED SINGLE-PLAYER GAME COOKING CHAOS - Kartikasari, Meivi; Hilmi, Aulia Wahida (UIN Ar-Raniry, 2024)
Cooking is the process of preparing food from its raw state until it is ready to be served, using heat to make it easier for the body to digest. However, nowadays, many teenagers lack an understanding of how to cook due to limited practice and a tendency to buy food from outside, which is considered more convenient. High levels of activity outside the home also contribute to the decreasing frequency of cooking among teenagers. Additionally, the convenience offered by food delivery applications, coupled with various attractive promotions, further contributes to the decline in interest in cooking. To address this issue, an educational single-player game application based on Android was developed, utilizing Unity 3D as the game engine and Blender for 3D object modeling. This application is designed to provide a more detailed cooking experience by offering 11 recipes that users can learn. Moreover, there is a mini-game in the form of a quiz to test users' understanding of the cooking process. Testing results show that this application successfully increased users' interest in learning to cook by 80.3%.